The Pandemic and Performance Index Accounting Reflections on Islamicicity in Dual Nation Islamic Banking - Lakilaki, Eogenie (Pusat Riset dan Inovasi Nasional, 2025)
This longitudinal comparative study investigates the ethical resilience of Islamic banks in Indonesia and Malaysia before and during the COVID-19 pandemic using the Islamicity Performance Index (IPI). Five performance dimensions, Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Islamic Investment Ratio (IIR), and Islamic Income Ratio (ISIR), are assessed to reflect the operationalisation of Maqasid al-Shariah values within Islamic financial institutions. Employing non-parametric Mann Whitney tests on annual report data from 11 Islamic banks over the 2017–2022 period, the study reveals statistically significant differences in PSR, IIR, and ISIR across the two timeframes and between countries, indicating varied institutional responses to ethical finance during crisis conditions. In contrast, ZPR and EDR remain statistically stable, suggesting limited change in social distribution and wealth justice mechanisms. These findings underscore the need to reevaluate the practical integration of Islamic ethical principles into crisis governance models and affirm the relevance of multidimensional Shariah-aligned metrics in evaluating financial integrity beyond profitability.